ECONOMIC ASPECTS REGARDING THE EXTRACTION OF WOOD USING HORSES: A CASE STUDY - Adrian Ioan TIMOFTE; Cristian Mihai ENESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study was embarked upon to evaluate the performance of micro broiler businesses in Calabar metropolis. The objectives of the study included; to describe the socioeconomic characteristics of broiler business owners, to analyse the effects of selected socio-economic characteristics of micro broiler business owners on the survival of micro broiler businesses in Calabar metropolis, and to analyze the marketing mix and managerial practices of business owners in Calabar metropolis. It made use of primary data obtained from a random sample of 112 micro broiler operators. The data were analyzed using descriptive statistics, and Ordinary Least Square Multiple regression approach. The result of analysis revealed that micro broiler business ownership is almost evenly distributed among males 47.32 percent and females 52.68 percent; and that more than half (56.25 percent) of the respondents are within the age brackets of 36-45 years. The study also revealed that respondents had one form of formal education or the other with tertiary education accounting for 75.89 percent. On the survival/competitive advantage of micro broiler firms in the study area, the result of Ordinary Least Square analysis showed that output of broiler, flock size, business experience, mortality and extension contact significantly contributed to a firm survival in broiler business. The study revealed that firms applied some management practices and marketing mix activities in operating their businesses. The managerial practices adopted and their mean weights included; planning (M = 3.80), organizing (M = 3.47), directing (M = 3.80), coordinating (M = 3.63) and controlling (M = 3.91). Also, the analysis showed that the marketing mix practices adopted and their mean values were; product (M = 3.23), price (M = 3.04), place (M = 3.77) and promotion (M = 2.26). The study shows that micro broiler operators showed positive attitude to all the management function and marketing mix practices. The study recommended that micro broiler operators should organize themselves into cooperative societies to enable them enjoy the benefits of economies of size and credit facilities from lending agencies. It was also recommended that relevant extension services should be made available to broiler operators to improve their skills and knowledge in broiler business operations. Policy action of government should be directed towards capacity utilization of operators. Also, subsidies should be provided for cost of feeds and day old chicks as well as instituting a flexible credit policy to reduce cost of production.